"DOING EVERYTHING POSSIBLE TO ENCOURAGE A BRITISH SENTIMENT": The Rise of Film Censorship and Regulation of Picture Houses in British Columbia, 1910-15. - MCILROY, BRIAN (BC Studies)
The article traces the evolution of British Columbia's film censorship and regulation of picture houses during the period 1910-1915. Topics include sociologist Renisa Mawani's argument on the racialization of policies and their interpretation within the rise of film censorship in the province, a comparison of film censorship between Toronto and British Columbia, and concerns about the pro-British attitude of the British Columbia government.